DEVELOPMENT AND VALIDATION OF STABILITY-INDICATING REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE ESTIMATION OF LEDIPASVIR IN BULK AND TABLET DOSAGE FORM - R GHANTE, MINAL; D SAWANT, SANJAY; SHINDE, AMOLDEEP; GODSE, SHITAL; S NIKAM, VANDANA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to develop a stability-indicating reverse-phase high-performance liquid chromatography (RP-HPLC) method for the estimation of ledipasvir (LDP) in bulk and tablet formulation. Methods: Stability-indicating RP-HPLC method was developed and validated for the estimation of LDP in bulk and tablet formulation. RP-HPLC was carried out on HiQ SiL C18 columns (250 mm × 4.6 mm, 5 μ particle size) using mobile phase acetonitrile:1 mM ammonium acetate buffer in the ratio of 90:10 v/v at a flow rate of 1 ml/min. The analytes were monitored using MD 2010 PDA detector at 333 nm. Results: The retention time was found to be 3.843 min. The proposed method was found to be having linearity in the concentration range of 5–30 μg/ml. The number of theoretical plates obtained was 4236.50 which indicate the efficient performance of the column. The limit of detection was 0.305 μg/ml and limit of quantification was 0.923 μg/ml, which indicate the sensitivity of the method; the high percentage recovery indicates that the proposed method is highly accurate. The developed method has been validated according to the ICH guidelines and found to be simple, specific, precise, and accurate. Conclusion: The proposed method is precise, accurate, and stability indicating. Therefore, the proposed method can be used for routine quality control and analysis of LDP during stability studies in bulk samples and tablet dosage forms.